Konsep Poligami Dalam Hermeneutika Amina Wadud : The Concept of Polygamy in the Hermeneutics of Amina Wadud - Rizki Afrianto Wisnu Wardana; Wendi Parwanto (ISTIDLAL, 2023)
Scientific advances occur in all disciplines. The sciences of the Qur'an are no exception. In the West, a woman was born who continues to shock the Islamic world to this day. The name is Amina Wadud. He is a professor of Islamic Studies who leads Friday prayers as an imam, both the imam and the speaker are women, and the congregation is made up of both men and women. Only Amina Wadud dared to lead Friday prayers, more than 1,400 years after the Prophet Muhammad preached. Amina Wadud didn't do this haphazardly, but she also had reasons. Its foundation is monotheistic hermeneutics. A person's marital status should not affect his or her ability to worship; as long as he is monotheistic, he is allowed to worship. In addition, the geographic environment in which Amina Wadud lives is the main reason for doing so. This study aims to consider Amina Wadud's views on polygamy and women's rights based on Islamic Sharia. The method used is descriptive qualitative. This research is included in the category of heritage research (library research), which collects data through books, articles, writings related to research. Research results show that polygamy is allowed under certain circumstances. Which relates to the custody process.